2021
DOI: 10.1002/er.7614
|View full text |Cite
|
Sign up to set email alerts
|

NiCo 2 O 4 ‐rGO /Pt as a robust nanocatalyst for sorbitol electrooxidation

Abstract: A ternary nanocatalyst consisting of nickel cobalt oxide (NiCo 2 O 4 ), reduced graphene oxide (rGO), and platinum (Pt) was introduced as a promising catalyst for application in the sorbitol oxidation reaction (SOR) process for use in fuel cells. Other catalysts such as NiCo 2 O 4 , NiCo 2 O 4 -rGO, and NiCo 2 O 4 /Pt were prepared for comparison. The structure and morphology of the synthesized nanocatalysts were examined by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It is this feature that makes renewable energy from sources including solar, ocean, hydro and plant materials very crucial for reducing carbon dioxide emission (Salarizadeh et al, 2022). It also guarantees reliable energy supply than fossil fuel (Askari et al, 2022). Regarding trade openness, it has been documented that its effect on energy intensity is inconclusive as it can increase or reduce energy intensity depending on whether it facilitates or inhibits efficiency (Adom, 2015a(Adom, , 2015b(Adom, , 2015c.…”
Section: Introductionmentioning
confidence: 99%
“…It is this feature that makes renewable energy from sources including solar, ocean, hydro and plant materials very crucial for reducing carbon dioxide emission (Salarizadeh et al, 2022). It also guarantees reliable energy supply than fossil fuel (Askari et al, 2022). Regarding trade openness, it has been documented that its effect on energy intensity is inconclusive as it can increase or reduce energy intensity depending on whether it facilitates or inhibits efficiency (Adom, 2015a(Adom, , 2015b(Adom, , 2015c.…”
Section: Introductionmentioning
confidence: 99%
“…For Mn 3 O 4 -CeO 2 -rGO, it was also observed that the anodic peak current density increased up to a scan rate of 90 mV/s, and after that, the current density decreased. It is likely that at higher scan rates, the electrolyte and methanol do not have enough time to fully engage with the catalyst and penetrate to its core, reducing current density [ 49 ]. The current density for Mn 3 O 4 -CeO 2 at scan rates of 10, 70, and 110 mV/s were 5.9, 8.8, and 7.9 mA/cm 2 , respectively, and for Mn 3 O 4 -CeO 2 -rGO at scan rates of 10, 90, and 110 mV/s were 11.6, 17.7, and 16.05 mA/cm 2 (the selected scan rates are the lowest, optimal, and the maximum scan rates, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Carbon materials, especially reduced graphene oxide (rGO), have excellent electrical conductivity which can improve the metal oxide properties. [ 31 ] Moreover, due to high surface area, rGO can be an attractive choice for promoting the electrocatalytic effects of metal oxide composites. [ 32,33 ]…”
Section: Introductionmentioning
confidence: 99%
“…[30] Carbon materials, especially reduced graphene oxide (rGO), have excellent electrical conductivity which can improve the metal oxide properties. [31] Moreover, due to high surface area, rGO can be an attractive choice for promoting the electrocatalytic effects of metal oxide composites. [32,33] In this study, NiO-Co 3 O 4 (NC) and NiO-Co 3 O 4 -rGO (NCR), as two metal component nanocatalysts, were synthesized by a hydrothermal method and the structure of the nanomaterials was characterized by complementary techniques.…”
Section: Introductionmentioning
confidence: 99%